Colorectal cancer in Crohn’s colitis is associated with advanced tumor invasion and a poorer survival compared with ulcerative colitis: a retrospective dual-center study - Vetter, Leonie E.; Merkel, Susanne; Bénard, Alan; Krautz, Christian; Brunner, Maximilian; Mittelstädt, Anke; Schlegel, Nicolas; Wiegering, Armin; Germer, Christoph Thomas; Weber, Klaus; Grützmann, Robert; Weber, Georg (International Journal of Colorectal Disease, 2020)
Purpose: Colorectal cancer is a well-recognized complication of inflammatory bowel diseases (IBD), such as ulcerative colitis (UC) and Crohn’s colitis (CC). In this study, we assess the clinico-pathological features and outcomes of patients with colorectal cancer from UC in comparison with CC. Methods: Data of all patients with colitis-associated cancer (CAC) who underwent surgery at Erlangen or Würzburg University Clinic between 1995 and 2015 were selected. Clinical, histopathological, and survival data were analyzed retrospectively. Results: Of all 88 patients with CAC, 20 patients had Crohn’s colitis and 68 patients had ulcerative colitis. We observed a young median age at tumor diagnosis (49.5 years UC; 45.5 years CC, p = 0.208) in both diseases and a long median disease duration before CAC (19 years UC; 18 years CC; p = 0.840). Patients with CC suffered more often from rectal cancer (14 (70.0%) in CC; 23 (33.8%) in UC; p = 0.005) and advanced tumor stages (8 (47.0%) pT4 in CC; 14 (25.0%) pT4/ypT4 in UC; p = 0.008). Five-year overall survival rate was 39.3% for CC and 67.1% for UC (p = 0.009 for difference between the groups). Survival did not differ significantly between UC and CC in the multivariate analysis after correction for UICC tumor stage. Conclusion: CAC in CC showed advanced tumor stages associated with reduced survival compared with CAC in UC. This may be explained by less intense surveillance in patients with CC leading to delayed cancer diagnosis.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Colorectal cancer; Crohn’s colitis; Ulcerative colitis